'Remediation of pre-clerkship clinical skill performance using a hybrid coaching model'. Issue 1 (1st January 2021) - Yonder, Sarah; Pandey, Jyotsna
ABSTRACT: Substance We reviewed the effect of a hybrid remediation model combining co-regulated learning and deliberate practice on future exam performance of pre-clerkship medical students who had been unsuccessful on a previous clinic skills exam. With this remediation model, we aimed to strengthen students' self-regulated learning to improve future exam performance and support sustained and improved learning. Educational problem addressed : Observing that some students who initially performed well post remediation with deliberate practice, still struggled on future exams, we looked to address a method that could improve both short-and long-term clinical skills learning success with sustained performance. Intervention outcome : Comparing the remediated students' exam scores pre- and post-coaching to their cohort's performance, we observed the majority of students post remediation performed above their cohort's exam average. Lessons learned : Combining learning models resulted in improved learning outcomes.